Perubahan Gaya Hidup Pada Masa Pandemi Covid-19: Gerakan Berkebun Di Desa Kesiman Kertalangu, Kecamatan Denpasar Timur (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2022)
The Covid-19 pandemic has had an impact on a several of people's lives, starting from the economy, health, and socio-culture. Rational choice theory by James S. Coleman (1989) as a scalpel to analyze lifestyle changes during the Covid-19 pandemic through the gardening movement in Kesiman Kertalangu Village, East Denpasar District. In this case, the people of Kesiman Kertalangu Village are able to maximize plant seeds from the Green majalagu program and home yards as a priority.The Green Majalangu Program activity is the distribution of plant seeds, organic fertilizer, and polybags for free to members of the Green Majalangu group and the people of Kesiman Kertalangu Village. This program was successfully carried out by the community by selling the harvest and distributing the harvest to relatives to support their daily needs. In addition, the gardening movement also has an impact on people's lifestyles during the pandemic.